Quality and safety of value added milk and dairy products - Kurwijila, Lusato R.; Birungi, Rosemirta; Makokha, S.; Musahara, H.; Otika, L.; Adissu, A.; Omore, Amos O. (Association for Strengthening Agricultural Research in Eastern and Central Africa, 2011)
Most Sub-Saharan countries including those in the ASARECA region are net importers of dairy products. Most products are imported from Europe and South Africa. In Southern Sudan, nearly all value added products are imported. At the same time, there is a growing demand for quality dairy products by the growing population and the tourist market. The unmet demand is providing opportunities for value addition. However, significant technical and institutional barriers continue to limit the exploitation of these benefits by small scale producers and small and medium scale enterprises (SMEs) engaged in value addition activities. A study characterizing value chains for both conventional and niche markets for dairy and meat products was carried out in Ethiopia, Kenya and Tanzania in 2006 and in Rwanda, Uganda and Southern Sudan in 2010. The main objective of the project is to enhance the capacity of small and medium scale enterprises to meet demand for quality and safety of the various value chain actors and regulatory requirements. Major concerns and opportunities for value addition are presented here to stimulate action by producers, processors and traders on key pertinent issues regarding the quality and safety of milk and dairy products produced and marketed by small and medium enterprises.